Balancing omega-6: Omega-3 ratios in oilseeds - Chirmade, T. P.; Sanghi, S.; Rajwade, A .V.; Gupta, V. S.; Kadoo, N. Y. (Omega-3 fatty acids: keys to nutritional health, 2016)
Fats and oils are the essential constituents of human diet, and nearly 80 % of these are obtained from plants. The predominant fatty acids present in plant oils are saturated and unsaturated compounds with straight aliphatic chains of carbon atoms and a single carboxyl group. Depending on the position of the first double bond from the methyl end in the fatty acyl chain, the mono- and polyunsaturated fatty acids can be denoted as -9, -6, or -3. Excess consumption of -6 fatty acids has greatly and unfavorably increased the -6: -3 ratio up to 25:1, which is associated with prevalence of many negative health effects, including cardiovascular diseases, cancer, osteoporosis, and inflammatory and autoimmune diseases. Because the -3 fatty acids (FAs) are the precursors for synthesis of anti-inflammatory eicosanoids, balancing the -6: -3 ratio is vital. The easiest approach to achieve this would be consumption of oils rich in -3 FAs, such as linseed oil. Alternatively, the fatty acid biosynthetic pathway in plants producing high -6 FAs can be altered by biotechnological means, so that they produce higher proportion of -3 FAs. This chapter describes the current knowledge of the fatty acid biosynthesis pathway in plants, including the genes involved, their temporal and spatial expression patterns, and various fluxes that they drive. The choice of oilseeds, genes, and promoters for modulating the fatty acid biosynthesis flux from -6 to -3 fatty acids is also dealt with. The potential hurdles in achieving these and possible solutions have also been described.